Architecture 101 : from Frank Gehry to Ziggurats, an essential guide to building styles and materials - Bridge, Nicole (Avon, Massachusetts : Adams Media, 2015)
Architecture 101 cuts out the boring explanations, and instead provides a hands-on lesson that keeps you engaged as you explore the world's greatest structures.
Includes index.
Keywords: ARCHITECTURE. -- HISTORY; ARCHITECTURE / REFERENCE; DESIGN / REFERENCE